Luis mayor (Pitangus sulphuratus) en el Altiplano Mexicano - Ramírez-Albores, Jorge E.; Chapa-Vargas, Leonardo; Jasso-Gordoa, María del Carmen (Instituto de Ecología, A.C., 2016)
The Great kiskadee (Pitangus sulphuratus) has a continuous distribution in both slopes of Mexico, mainly in tropical zones. As a result of monthly samplings from December 2006 to August 2013, we report the occurrence of this species in eastern Aguascalientes and the Highland Plateau region of San Luis Potosi. Based on these records, we suggest that this species can be considered as a resident for this region, thus suggesting that its geographic distribution could be extended to the central plateau of Mexico.